Practices of Jeddah Residents Regarding the Disposal of Unused and Expired Medications: A Community-Based Survey - Afnan A. Abuassonon,; Bayader S. Kalkatawi,; Lamia S. Alzahrani,; Basma G. Eid,; Thikryat A. Neamatallah, (Journal of King Abdulaziz University: Medical Sciences, 2019)
Inappropriate disposal of stored medications leads to an increased risk of environmental toxicity. This study aims to examine practices of Jeddah residents with regard to disposing unused and/or expired medications and to view their opinions about the presence of drug take-back centres. Over a three-month period, 771 participants completed an online questionnaire, that focused on disposal methods and the importance of having drug retrieval centres. The data demonstrated that 91.57% of the participants reported discarding their expired medications in household waste, and 2.98% of them return their medications to hospitals or pharmacies. With respect to unused medications, 67.07% of the participants disposed of them in household waste, and only 10.84% donated their medications. This improper practice, however, contradicted the fact that 92.35% of the respondents were interested in knowing the appropriate methods of disposing. In addition, 90.66% agreed to the need for drug take-back centres. This study demonstrated that a low percentage of respondents knew about correct medication disposal. This emphasizes the need for the Ministry of Health, the pharmaceutical industry and pharmacies to collaborate on a national program about the proper methods of medication disposal and to initiate drug retrieval programs.